ANALISIS PENGEMBANGAN SUMBER DAYA AIR DAS TUKAD SABA DENGAN DIBANGUNNYA WADUK TITAB DI KABUPATEN BULELENG - Sari, Siti Nur Indah; Yekti, Mawiti Infantri; Norken, I Nyoman (JURNAL SPEKTRAN; Vol 8 No 1 (2020): VOL. 8, NO. 1, JANUARI 2020, 2020)
The Saba river basin has an area of ??69.54 km 2 and the length of the drainage is 36 km. The river drainage area is a hilly area, so that rainwater flows quickly which then becomes a flood. The land condition in the inundation area generally consists of rice fields that depend on rain, there is no technical irrigation system so that the cropping pattern depends on the rain. So to overcome this problem a Titab Reservoir was built. The Titab Reservoir serves as the supply of irrigation water for DI Saba with an area of ??1,396.40 ha and Pulp of 398.42 ha, raw water as much as 0.35 m 3 /s and PLTA with 2 x 0.75 MW. Given the importance of the benefits of the Titab Reservoir, a study of the reservoir capacity of the Titab Reservoir was conducted. The analysis begins with calculating the reliability discharge from measured discharge data, obtained Q 80 of 2.01 m 3 /dt. Furthermore, calculating irrigation needs, while water and hydropower needs are used from existing planning data. Then do the simulation using the RIBASIM program. The simulation results show scenario 2 produces a reliability level of 83.33%, scenario 3 produces a reliability level of 82.22%, and scenario 4 produces a reliability level of 58.54%. Scenario 2 is the optimum result. Furthermore, verification of the RIBASIM model is needed using observational discharge data at the Saba dam. The verification results show that the data accuracy is quite good with a correlation coefficient of 0.74 and determination of 0.55.